FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA DENGAN MODEL KOREKSI KESALAHAN ENGLE-GRANGER (PENDEKATAN MONETER) - Eni Setyowati (Muhammadiyah University Press, 2003)
Exchange rate measures the value of a certain foreign exchange from other foreign exchange's perspective. As the condition of economic changes, the exchange rate ma change substantially. The decrease of the value of a foreign exchange is called depreciation and the increase value of a foreign exchange is called appreciation.The equilibrium exchange rate will change along with the change of demand and supply. Factors causing the change of demand and supply curve among others are the amount of money supply, relative gross domestic product (GDP) and the level of relative interest rate.The research is aimed to analyze the influence of variables of Indonesian money supply, American money supply, Indonesian real Gross Domestic Product, American real Gross Domestic Product, deposits interest rate and LIBOR (London Interbank Offer Rates on SDR Deposit) both in short and long terms.One of the ways to analyze the influence of short term and long term is by developing the dynamic model. In this research, the analyzes of dynamic model was conducted with ENGEL-GRANGER ERROR CORRECTION MODEL approach which was developed by ENGEL-GRANGER (1987) based on GRANGER REPRESENTATION THEOREM.The ECM analyzes was chosen not only because of its ability to solve the problem of time series which is not stationer, and spurious regression and spurious correlation in the economic analyses but also its ability to discuss the consistence of empiric model with economic theory. Beside, ECM concept is also thought to be more realistic in observing the development of economics variables from the result of the analyzes during the time of observation. It was known that long-term exchange rate is influenced by Indonesia real Gross Domestic Product and the number of Indonesian money supply. The variable of Indonesian real Gross Domestic showed the significant result and the signal test was convenient with the theory. The variable which influence